2018
DOI: 10.1111/epi.14494
|View full text |Cite
|
Sign up to set email alerts
|

Perampanel in patients with refractory and super‐refractory status epilepticus in a neurological intensive care unit: A single‐center audit of 30 patients

Abstract: In refractory status epilepticus (SE), γ-aminobutyric acidergic drugs become less effective and glutamate plays a major role in seizure perpetuation. Data on the efficacy of perampanel (PER) in treatment of refractory SE in humans are limited. Here, we present a single-center case series of patients with refractory SE who received PER orally in an intensive care unit. We retrospectively analyzed treatment response, outcome, and adverse effects of all patients with refractory SE in our Neurological Intensive Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 28 publications
3
43
0
Order By: Relevance
“…[19][20][21][22] Rohracheretalreportedtreatmentresponsein5/30(16.7%)perampanel-treated patients with RSE and SRSE, of whom two received higher doses (20 and 24 mg); however, decreased bioavailability and late administration may have diminished the potential effects of perampanel. [19][20][21][22] Rohracheretalreportedtreatmentresponsein5/30(16.7%)perampanel-treated patients with RSE and SRSE, of whom two received higher doses (20 and 24 mg); however, decreased bioavailability and late administration may have diminished the potential effects of perampanel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22] Rohracheretalreportedtreatmentresponsein5/30(16.7%)perampanel-treated patients with RSE and SRSE, of whom two received higher doses (20 and 24 mg); however, decreased bioavailability and late administration may have diminished the potential effects of perampanel. [19][20][21][22] Rohracheretalreportedtreatmentresponsein5/30(16.7%)perampanel-treated patients with RSE and SRSE, of whom two received higher doses (20 and 24 mg); however, decreased bioavailability and late administration may have diminished the potential effects of perampanel.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the rat lithium-pilocarpine model of SE have suggested that perampanel may have efficacy in terminating prolonged seizures 17,18 while providing neuroprotection, though the level of neuroprotective effects varied by region. 15 However, while clinical cases of perampanel use for the treatment of patients with SE have been reported, [19][20][21][22] there are currently few published case reports assessing the effectiveness of perampanel in SE, as reviewed previously. Furthermore, modified expres-sionoftheAMPAsubunitsGluA1andGluA2andalteredCa 2+ permeability have been observed in animal models of SE.…”
Section: Intermsoftheunderlyingpathophysiologysemightarisefrommentioning
confidence: 99%
“…Findings from phase III studies suggest that PER 4 mg is probably the lowest effective dose in patients with partial‐onset seizures, with increased efficacy at the 8‐mg and 12‐mg doses . Review of the literature shows five articles on the use of this agent in SE (Table ) . One study analyzed PER use in 12 patients with RSE in a single neurology ICU in Austria.…”
Section: Discussionmentioning
confidence: 99%
“…30 patients that received perampanel as add‐on treatment in refractory and super‐refractory SE from Sept 2012 and Feb 2018…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation